PKM SOSIALISASI HUKUM TENTANG TERTIB ADMINISTRASI PERTANAHAN DAN PERHITUNGANNYA DI DESA SINARMUKTI - Nurul Qolifah; Hadi Haerul Hadi; Uluhiyah Uluhiyah; Ahmad Hilwani; Asnawi Asnawi; Harry Qurba; Anton Nasrullah (Yayasan Education and Social Center, 2021)
Land registration is a form of land administration regulated in the Basic Agrarian Law (UUPA). As stated in the UUPA, land registration must be carried out because the purpose of land registration is very beneficial for land rights holders. However, there are still individuals who have not completed the land registration process in Sinarmukti Village. This is an unorganized form of land administration. Many factors cause the absence of orderly land administration, one of which is the lack of public understanding of agrarian laws and regulations, especially regarding land registration which is one component of land administration. Many problems may arise if land registration is not carried out; for example, a common problem in Indonesia is disagreement (land disputes). Land disputes continue to occur; one of the causes is the irregularity of land administration in the past. This problem can happen anywhere and can appear in the Sinarmukti Village community. Therefore, agricultural law counseling activities are carried out to increase public understanding of agrarian law, especially the orderly land administration with land registration. These activities are carried out through the use of an online seminar system or webinars. The general public can follow the guidelines from the webinars so that the public becomes aware and knows about land administration